The Role of Bureaucratic Ethics in Preventing Corruption in Regional Government Environments - Dewi Tjandraningsih; Juhary Ali (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study examines the role of bureaucratic ethics in preventing corruption within local government institutions in Indonesia. Bureaucratic ethics is regarded as a fundamental value framework that guides public officials to perform their duties based on integrity, accountability, transparency, and responsibility. In practice, the lack of ethical commitment and weak internal control systems have often created opportunities for corrupt behavior, particularly in budget management, public services, and licensing processes. This research employs a qualitative-descriptive approach through literature analysis on bureaucratic ethics, public administration, and corruption prevention. The findings reveal that ethical standards significantly influence bureaucratic behavior and contribute to strengthening institutional integrity, reducing abuse of power, and enhancing public trust. Strengthening bureaucratic ethics requires a combination of ethical education, strict enforcement of disciplinary rules, improved supervision, and the establishment of a transparent administrative culture. Therefore, reinforcing ethical values is essential to build a clean, professional, and corruption-resistant local bureaucracy.